Papers from the Alan Rawel CIPR academic conference - Wood, Emma H. (Journal of communication management, 2006)
This e-book features 7 of the accepted papers from The Alan Rawel CIPR Academic Conference 2005 - New thinking in public relations research and practice: Partnering academia with industry. From a mixture of academics and practitioners.